Metacognition in Relation to Teacher Competencies as Perceived by Students of Different School Types - Kapadia, Rashida (JOURNAL OF INDIAN EDUCATION, 2013)
This work is aimed at studying and comparing metacognition and perceived teacher competency of secondary school students. Data was collected from Class IX students of different school types i.e., SSC, ICSE and CBSE schools across Greater Mumbai. Results show that students of all the school types, SSC, ICSE and CBSE, consider that their teachers are equally competent. They consider their teachers to possess social, technical as well as affective competencies. Analysis was done for total and component-wise scores for metacognition and perceived teacher competency. A significant, direct, positive correlation was found between total metacognition and total teacher competency scores. Component-wise analysis revealed technical competency component of teacher competency-to be a strong and significant predictor of all the components of metacognition for total sample and for SSC and ICSE students. This indicates that the teachers’ communication skill, evaluation ability, classroom management, mastery over content and ability to organise information is related to metacognition of students. The need for competent teachers for supporting student’s metacognition is endorsed.